The Role of Mediation in Civil Case Settlement Banyuwangi Court - Ainu Rofiq (Formosa Journal of Applied Sciences, 2023)
It is clear from the research and analysis that the Banyuwangi District Court's procedure for settling Civil Case No. 12 / Pdt.G / 2018 / PN. Byw went through three stages and was in compliance with PERMA No. 01 of 2008 concerning Mediation Procedures in Courts. The Pre-Mediation Stage, Mediation Process Stage, and Post-Mediation Stage are some of these stages. In Civil Case No. 12/Pdt.G/2018/PN. A violation of contract and an illegal act formed the basis of the complaint. At the first trial in this civil action, the court attempted to mediate a settlement for the parties, and the mediation's conclusion was mutually agreed upon, stated, and affirmed in the judgment and stipulation of the Deed of Peace No.12/Pdt.G/2018/PN.Byw.